2021
DOI: 10.1111/gcb.15533
|View full text |Cite
|
Sign up to set email alerts
|

Plastic ingestion by marine fish is widespread and increasing

Abstract: Plastic pollution has pervaded almost every facet of the biosphere, yet we lack an understanding of consumption risk by marine species at the global scale. To address this, we compile data from research documenting plastic debris ingestion by marine fish, totaling 171,774 individuals of 555 species. Overall, 386 marine fish species have ingested plastic debris including 210 species of commercial importance. However, 148 species studied had no records of plastic consumption, suggesting that while this evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(84 citation statements)
references
References 68 publications
(103 reference statements)
1
82
0
1
Order By: Relevance
“…Methods used for detection of microplastic have varied over time, with improvements in technical abilities since microplastic research has increased in popularity (Savoca et al, 2021). Some researchers used only naked-eye (e.g., Forrest and Hindell, 2018) or microscope detection (e.g., Cannon et al, 2016) to visualize the gastrointestinal tract content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods used for detection of microplastic have varied over time, with improvements in technical abilities since microplastic research has increased in popularity (Savoca et al, 2021). Some researchers used only naked-eye (e.g., Forrest and Hindell, 2018) or microscope detection (e.g., Cannon et al, 2016) to visualize the gastrointestinal tract content.…”
Section: Discussionmentioning
confidence: 99%
“…Microplastic ingestion in marine fish is well documented (Markic et al, 2019;Sequeira et al, 2020;Savoca et al, 2021), with field studies reporting microplastic ingestion in wild-caught fish of both commercial and non-commercial interest from a broad range of trophic levels, habitats and benthic zones (Foekema et al, 2013;Nadal et al, 2016;Murphy et al, 2017;Baalkhuyur et al, 2018;Burkhardt-Holm and N'Guyen, 2019;Garnier et al, 2019). Despite this, the literature surrounding microplastic in fish sold through seafood markets and supermarkets is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microplastics have been found in the guts of amphipods in the hadal zone, and even in the deepest trench in the ocean, the Mariana trench, all studied amphipods had ingested microplastics (Jamieson et al, 2019). In addition, Choy et al (2019) found that the concentration of microplastics in the water column, measured down to 1,000 m, was highest between 200 and 600 m. Mesopelagic lanternfishes were recently shown to have high levels of plastic ingestion and their diel migration is likely an important transport mechanism for the plastic particles into the deeper waters (Savoca et al, 2021).The ingestion of plastics has a host of negative effects that are likely to impede health of the individual animals, with incumbent effects on biodiversity (Browne et al, 2013;Deudero and Alomar, 2015;Fossi et al, 2018).…”
Section: Threats To Biodiversity In the Deep Seamentioning
confidence: 89%
“…Detrimental impacts on fish populations have been shown to result from noise disturbance and pollution from small motor boats (Whitfield and Becker, 2014). However, while plastic ingestion by marine fish, including those of commercial importance, is increasing globally, there is no evidence as yet of negative effects on fish populations (Lusher et al, 2017;Savoca et al, 2021). Small pelagic fisheries in Timor-Leste are orders of magnitude smaller than the major sardine fisheries elsewhere in the region-the entire national fisheries production (all species) was estimated to be under 2,500t in 2017 (López-Angarita et al, 2019).…”
Section: Fluctuations In Sardine Landings and Perceived Driversmentioning
confidence: 99%